Effects of fiber content on crystallization behavior and mechanical properties for fiber-reinforced microcellular injection molding combined with in-mold decoration process - Shengrui Yu; Haitao Hua; Lei Xu; Senzhen Song; Tianyu Zhang; Linan He; Chunfa Dong; Qingzhou Li; Fei Chen; Wen Han; Lanyu Zeng; Huamin Zhou (Materials & Design)
Fiber-reinforced microcellular injection molding combined with in-mold decoration (FR-MIM/IMD) is an emerging technique for producing lightweight polymer components with excellent mechanical performance and surface quality. However, unlike conventional injection molding (CIM), the FR-MIM/IMD process involves complex interactions among supercritical fluid, polymer melt, and reinforcing fibers, complicating the control of crystallization and structure–property development. In particular, the effects of varying fiber contents on melt behavior, cellular structure, and crystallization dynamics remains poorly understood. This study investigates how glass fiber (GF) content influences melt flow characteristics, microstructure, crystallization behavior, mechanical performance, and apparent density in nitrogen (N2)-foamed polypropylene (PP)/GF composites, using simulations and experiments. Results show that increasing fiber content elevates melt temperature, while viscosity peaks at 20 wt% before declining. Higher fiber content promotes fiber alignment, reduces cell size, increases cell density, and improves cell uniformity. Crystallization temperature rises with fiber content, although the crystallization rate slows. Both crystal size and β-crystal content peak at 20 wt%. Tensile and flexural strengths increase significantly—by 193.4 and 157.4% from 0 to 30 wt%, respectively—while elongation at break peaks at 10 wt%. Apparent density increases by 26.3%. These findings provide insights for optimizing FR-MIM/IMD process and tailoring composite performance.